EFFECTIVENESS OF THE CONSIGNMENT MECHANISM IN CREATING LEGAL CERTAINTY IN LAND ACQUISITION FOR PUBLIC INTERESTS - Junpiter Tambun; Yalid; Indra Afrita (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze the application of the consignment mechanism in land acquisition for public interest in the construction of the Balairaja Toll Gate, Bengkalis Regency, based on the principles of legal certainty and protection of land rights, and to reconstruct a more ideal consignment mechanism. The study used sociological legal methods. The results indicate that consignment provides legal certainty for the government in continuing development when compensation is refused or land rights are disputed. However, its implementation still faces various obstacles, such as suboptimal deliberation, lack of transparency in compensation assessments, limited community participation, and the tendency to use consignment as an instrument for accelerating development. This situation has resulted in a balance between legal certainty, justice, and the protection of community rights that has not been fully realized. Therefore, reconstruction of the consignment mechanism is necessary by strengthening the deliberation function, increasing transparency and accountability in assessments, providing opportunities for comparative assessments (second appraisals), placing consignment as a last resort (ultimum remedium), strengthening oversight by the District Court, and improving the provisions in Law Number 2 of 2012 and its implementing regulations. This reconstruction is expected to achieve a balance between national development interests and the protection of community constitutional rights in accordance with the principles of a democratic state based on the rule of law.